2015
DOI: 10.1590/1983-21252015v28n303rc
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores De Qualidade Do Solo Sob Diferentes Sistemas De Uso Na Mesorregião Do Agreste Paraibano

Abstract: RESUMO -Os sistemas de cultivo modificam os atributos do solo, podendo alterar sua qualidade. O trabalho teve como objetivo avaliar as alterações nos atributos físicos, químicos e biológicos de solos sob sistemas de cultivo orgânico (solos cultivados organicamente há mais de sete anos), em conversão para orgânico e convencional, tendo como referência o solo sob mata, assim como identificar os atributos a serem utilizados como indicadores de qualidade do solo. Foram selecionadas três áreas de propriedades agríc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
32

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 21 publications
1
9
0
32
Order By: Relevance
“…Therefore, to the soil of the present study (Sand = 0,93 kg kg -1 ) the SLD is This way, techniques that enable BD decrease and, consequently, the porosity and aggregates stability increase, must be continuously used in the row spacing. Some areas under different use systems evaluated by Silva et al (2015) showed that BD is decreased when the organic cultivation or in conversion to organic is implemented, being indicative, possibly, of the greatest contribution of soil's organic matter, increasing microbial activity and improving the particles aggregation. Therefore, it is appropriated to suggest the adopted practices in the canopy region (as maintenance of the pruning residues from the crop) must be expanded to the row spacing of irrigated mango cultivation, just like occurred in alley cropping systems.…”
Section: Soil Physical Attributesmentioning
confidence: 99%
“…Therefore, to the soil of the present study (Sand = 0,93 kg kg -1 ) the SLD is This way, techniques that enable BD decrease and, consequently, the porosity and aggregates stability increase, must be continuously used in the row spacing. Some areas under different use systems evaluated by Silva et al (2015) showed that BD is decreased when the organic cultivation or in conversion to organic is implemented, being indicative, possibly, of the greatest contribution of soil's organic matter, increasing microbial activity and improving the particles aggregation. Therefore, it is appropriated to suggest the adopted practices in the canopy region (as maintenance of the pruning residues from the crop) must be expanded to the row spacing of irrigated mango cultivation, just like occurred in alley cropping systems.…”
Section: Soil Physical Attributesmentioning
confidence: 99%
“…Silva et al (2015) obtiveram resultados semelhantes em seu estudo e atribuíram a menor resistência a penetração observada nas camadas superficiais à exploração do sistema radicular das plantas e atividade biológica do solo.…”
Section: Resistência a Penetração (Rp)unclassified
“…Alguns atributos como pH, salinidade, carbono orgânico, fósforo assimilável e CTC, possibilitam o entendimento da dinâmica dos nutrientes e a relação com a fertilidade do solo. Indicadores biológicos fornecem um indicativo da microbiota do solo, a qual se relaciona diretamente com processos de decomposição, formação da matéria orgânica recalcitrante, ciclagem de nutrientes, atividade enzimática e microbiana Os bioindicadores de qualidade do solo têm a capacidade de responder às mudanças no solo, por exemplo, a avaliação da atividade microbiana têm sido amplamente utilizada devido à relação com o tipo de cobertura vegetal e sustentabilidade dos ecossistemas, sendo utilizado como indicador sensível de estresse ecológico ou dos processos de restauração do solo em ambientes naturais e nos agroecossistemas sob cultivo (SILVA et al, 2015a).…”
Section: Introductionunclassified